The Role of Kiai Leadership in Nahdlatul Ulama Islamic Boarding Schools: A Utilitarian Ethical Perspective - Munawar, Agus; Suryanto, Tulus; Syafril, Syafrimen; Koderi, Koderi (STIT Ahlussunnah Bukittinggi, 2025)
The Nahdlatul Ulama (NU) Islamic boarding schools (pesantren) in Lampung plays a vital role in religious education ‎and character building within the community. The leadership of the kiai in the pesantren is ‎not limited to the spiritual aspect, but also affects the social welfare of the surrounding ‎community. Therefore, it is important to explore the application of utilitarianism principles in ‎the kiai's leadership to improve the well-being of the community. This study aims to analyze ‎the role of kiai leadership in NU pesantren in Lampung and how the principles of ‎utilitarianism are applied in their leadership. The research method used is a qualitative ‎approach with a case study design. Data were collected through in-depth interviews with ‎kiais, pesantren administrators, and santri, as well as observations of the kiai's leadership ‎practices in the pesantren. The results show that the application of utilitarianism principles ‎in kiai leadership has proven to provide greater social benefits, both in education, economic ‎empowerment, and social policies that prioritize the common welfare. This study concludes ‎that kiai leadership based on utilitarianism principles can create a positive impact on the ‎pesantren community and its surroundings. Furthermore, these findings contribute to the ‎development of a leadership model based on social values and the well-being of the ‎community, which can be applied in other pesantren across Indonesia‎.